Graphite negative electrode material and preparation method thereof, and secondary battery
By combining the graphite core with a uniform amorphous carbon outer layer in the graphite negative electrode material, the problem of low charging rate of lithium-ion batteries is solved, and the material rate performance is significantly improved and the stability improvement is improved.
Patent Information
- Application Number
- CN202411889475.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-20
- Publication Date
- 2025-03-28
AI Technical Summary
The existing lithium-ion battery graphite anode materials have low charging rates during charging, and conventional coating methods are difficult to effectively improve the rate performance.
The graphite core is combined with a uniform amorphous carbon outer layer, and the Raman test is used to ensure AD/AG ≥ 1.0 and IQR ≤ 0.25, forming a uniform carbon cladding layer to improve the flux of the lithium ion embedded channel and the stability of the material.
The rate performance of graphite negative electrode material is significantly improved, the high current charge and discharge performance of the material is enhanced, and the compatibility with the electrolyte is improved.
Smart Images

Figure CN119725446A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of carbon material preparation, and in particular to a graphite negative electrode material and a preparation method thereof, and a secondary battery. Background Art
[0002] The rapid development of electric vehicles has put forward higher requirements for the fast charging capability of lithium-ion batteries. Since the commercialization of lithium-ion batteries, the most mature negative electrode material used is graphite negative electrode material.
[0003] At present, the common graphite negative electrode materials of lithium-ion batteries include natural graphite, artificial graphite and other types. During the charging process, Li + Migrate from the positive electrode to the negative electrode and embed into the layered structure of the graphite material to form LiC6 compound. The lithium insertion process of the negative electrode mainly includes Li + It consists of diffusion in the electrolyte and SEI membrane, charge exchange on the negative electrode surface, and diffusion of Li in the solid phase, which will directly affect the charging rate of lithium-ion batteries.
[0004] In order to increase the charging rate of lithium-ion batteries, the industry has adopted the surface coating of fast ion conductors such as Li3PO4 to modify graphite materials to improve the fast charging performance of graphite materials. However, this method of coating lithium phosphate is costly and has very strict process requirements. There are also problems such as uneven coating and unstable coating structure. At present, although the development of graphite negative electrode materials has gradually matured, the conventional use of coating and other means has limited improvement in rate performance. Therefore, it is necessary to comprehensively explore various factors from the raw material coke end to the finished product end to maximize the improvement of the rate performance of graphite materials. Summary of the invention
[0005] The purpose of the present invention is to provide a graphite negative electrode material and a preparation method thereof, and a secondary battery. The graphite negative electrode material has a certain optical structure and Raman spectrum parameters, and can improve its rate performance on the basis of ensuring the capacity of the graphite negative electrode material.
[0006] To achieve the above object, the first aspect of the present invention provides a graphite negative electrode material, comprising a graphite core and an amorphous carbon outer layer. The graphite negative electrode material satisfies the conditions AD / AG≥1.0 and IQR≤0.25 after Raman testing. Wherein AD / AG is the peak area ratio of the D peak and the G peak in the spectrum of the Raman test, IQR is the interquartile range of AD / AG, and the D peak is located at a wavelength of 1350cm -1 The defect peak, G peak, is located at a wavelength of 1580cm -1 Characteristic peaks of ideal graphite crystal.
[0007] Since the AD / AG of graphitized products is generally lower than that of carbonized products, the thicker the outer layer of amorphous carbon is within a certain range, the greater its AD / AG value. If the outer layer of amorphous carbon exists on the surface of the graphite core in an uneven or localized manner, a small-range multi-point scan during Raman testing will show that the D peak and G peak area ratio data are scattered and the difference is large, resulting in a low AD / AG value and a high IQR. If the outer layer of amorphous carbon exists in the form of a uniform surface coating, the surface structure and composition of the material are slightly different, the AD / AG value is small, and the IQR is small. The graphite negative electrode material of the present invention meets the conditions of AD / AG≥1.0, IQR≤0.25, indicating that the outer layer of amorphous carbon of the graphite negative electrode material of the present invention is uniformly coated.
[0008] The interlayer spacing of the amorphous carbon outer layer is larger than that of graphite and is arranged in disorder. As a uniform surface coating layer, it can provide lithium ion embedding channels in all directions with low embedding resistance, thereby improving the high current charge and discharge performance of the graphite negative electrode material. In addition, the active end face of the graphite core can also be reduced, thereby reducing the side reaction with the electrolyte and improving the compatibility of the graphite core with the electrolyte. Therefore, the graphite negative electrode material of the present invention can improve the rate performance of the material through the uniformity of the coating of the amorphous carbon outer layer.
[0009] As a technical solution of the present invention, the thickness of the amorphous carbon outer layer is 5 to 500 nm.
[0010] As a technical solution of the present invention, the specific surface area of the graphite negative electrode material is 0.5 to 2.0 m 2 / g.
[0011] As a technical solution of the present invention, the tap density of the graphite negative electrode material is 0.9-1.4 g / cm 3 .
[0012] As a technical solution of the present invention, the Dv50 of the graphite negative electrode material is 3 to 30 μm.
[0013] As a technical solution of the present invention, the interlayer spacing d002 of the graphite negative electrode material is 0.3355-0.3400 nm.
[0014] As a technical solution of the present invention, the graphite negative electrode material has a graphitization degree of 85-97%.
[0015] As a technical solution of the present invention, the graphite negative electrode material has an initial charging capacity of ≥320 mAh / g at 0.1C.
[0016] As a technical solution of the present invention, the first coulombic efficiency of the graphite negative electrode material at 0.1C is ≥90%.
[0017] As a technical solution of the present invention, the 1.0C / 0.1C capacity retention rate of the graphite negative electrode material is ≥70%.
[0018] As a technical solution of the present invention, the 2.0C / 0.1C capacity retention rate of the graphite negative electrode material is ≥55%.
[0019] As a technical solution of the present invention, the 3.0C / 0.1C capacity retention rate of the graphite negative electrode material is ≥35%.
[0020] As a technical solution of the present invention, the graphite core is artificial graphite.
[0021] As a technical solution of the present invention, the graphite core includes artificial graphite single particles and / or artificial graphite secondary particles.
[0022] A second aspect of the present invention provides a method for preparing a graphite negative electrode material, comprising the steps of:
[0023] ① Adding a small molecule nucleating agent to a carbon source, and then subjecting the carbon source to a coking reaction to obtain raw coke, wherein the raw coke satisfies the condition 1.2≤4×A+B<4.0 after optical tissue detection, wherein A and B represent the contents of a mosaic structure and a small domain structure in the optical tissue, respectively; the mosaic structure is a structure in which the medium color area size in the polarized image of the optical tissue is less than 30 μm, and the small domain structure is a structure in which the medium color area size in the polarized image of the optical tissue is between 30 and 50 μm;
[0024] ② subjecting the raw coke to a front-end processing step to obtain coke powder single particles or shaped secondary particles, wherein the front-end processing step includes at least one of a pulverizing step, a shaping step, a granulating step and a secondary shaping step;
[0025] ③ graphitizing the coke powder single particles or shaped secondary particles to obtain a graphitized product;
[0026] ④ The graphitized product and the carbon coating agent are mixed and then carbonized to obtain a carbonized product, and the carbonized product satisfies the conditions AD / AG≥1.0 and IQR≤0.25 after Raman testing, wherein AD / AG is the peak area ratio of the D peak and the G peak in the spectrum of the Raman test, IQR is the interquartile range of AD / AG, and the D peak is located at a wavelength of 1350cm -1 The defect peak of G peak is located at a wavelength of 1580cm -1 Characteristic peaks of ideal graphite crystal.
[0027] The preparation method of the present invention has at least the following technical effects.
[0028] (1) The present invention adds a heterogeneous small molecule nucleating agent on the basis of the carbon source. The small molecule nucleating agent acts as a non-uniform nucleation agent, and its nucleation volume is small, the nucleation work is small, the structural fluctuation and energy fluctuation required for nucleation are small, and nucleation is easy. Therefore, with the small molecule nucleating agent as a template, the carbon source molecules diffuse and adsorb to the small molecule nucleating agent, and it is easy to nucleate and develop into an intermediate phase body. After the coking reaction, raw coke with more mosaic structures and small domain structures can be obtained. The present invention can obtain raw coke that meets the condition of 1.2≤4×A+B<4.0 in optical tissue detection by regulating the nucleating agent.
[0029] (2) The coke with mosaic structure and small domain structure has the advantages of high softening point, high coking value and residual carbon rate, easy graphitization, etc., especially the graphite formed after high temperature heat treatment has fine crystallites, uniform grain size, uniform structure and high isotropy. Among them, the fine crystallites can ensure sufficient electrochemical reaction interface and promote the diffusion of lithium ions at the solid-liquid interface. At the same time, the small size greatly shortens the diffusion path of lithium ions, promotes the solid phase diffusion process within the particles, reduces concentration polarization, and is conducive to improving the rate performance of graphite negative electrode materials. Therefore, the rate performance of graphite negative electrode materials can be greatly improved by high content of mosaic structure and small domain structure.
[0030] (3) In addition, in addition to the mosaic structure and small domain structure, the raw coke can also be a large domain structure and a fiber structure. The large domain structure and the fiber structure have a high degree of preferential orientation and few defects, which are beneficial to the growth and development of microcrystals during the graphitization process. In addition, a high degree of graphitization is beneficial to the capacity improvement of the graphite negative electrode material. Therefore, to improve the rate performance on the basis of ensuring the capacity of the graphite negative electrode material, it is necessary to control the content distribution of the mosaic structure, small domain structure, large domain structure and fiber structure. Therefore, the present invention can achieve a higher capacity and meet the high rate of the material by regulating the nucleating agent to obtain raw coke that meets the condition 1.2≤4×A+B<4.0 in optical tissue detection.
[0031] (4) The present invention obtains raw coke that meets certain optical structural conditions. Although it can achieve fine graphite crystallites, uniform grain size, uniform structure, and high isotropy, during the use of the battery, lithium ions are embedded between graphite layers from the end faces. As the amount of embedding increases, it will inevitably lead to volume expansion in the direction perpendicular to the end faces. The present invention further provides an amorphous carbon layer on the outer layer to relieve internal stress and provide sufficient strength to maintain the stability of the graphite structure, thereby maintaining the material's cycle performance. By controlling the graphite negative electrode material to meet the conditions AD / AG≥1.0, IQR≤0.25, that is, forming a uniform carbon coating layer, it can not only effectively relieve internal stress and increase strength, but also as a uniform surface coating layer, it can provide lithium ion embedding channels in all directions with low embedding resistance, thereby further improving the large current charge and discharge performance of the graphite negative electrode material.
[0032] Therefore, the inventors of the present invention comprehensively consider the synergistic effects of the internal optical structure of the raw coke and the uniformity of the surface coating layer on the performance of the graphite negative electrode material, and in the preparation method, through the regulation of small molecule nucleating agents and carbonization, a raw rubber with a certain optical structure and a uniformly coated amorphous carbon outer layer can be obtained, that is, the optical structure detection satisfies the condition 1.2≤4×A+B<4.0, and the Raman test satisfies the condition AD / AG≥1.0, IQR≤0.25. Under this condition, the migration of lithium ions in the multi-channel, low-resistance, and short-path conditions inside the graphite can be controlled, the uniformity of the outer layer coating can be regulated, and sufficient strength can be given to the graphite to maintain the stability of the structure, so that the graphite negative electrode material has a better rate performance on the basis of maintaining the capacity.
[0033] As a technical solution of the present invention, the small molecule nucleating agent is 0.01-1.00% of the mass of the carbon source.
[0034] As a technical solution of the present invention, A≥0.3.
[0035] As a technical solution of the present invention, B≥0.2.
[0036] As a technical solution of the present invention, the carbon source is coal tar pitch or oil slurry.
[0037] As a technical solution of the present invention, the particle size of the small molecule nucleating agent is ≤50 μm.
[0038] As a technical solution of the present invention, the small molecule nucleating agent includes graphite fine powder, graphitizable coke fine powder, and transition metal fine powder.
[0039] As a technical solution of the present invention, the coking reaction is carried out in a coking tower, the pressure of the coking tower is 50 to 700 KPa, and the coking time is 8 to 30 hours.
[0040] As a technical solution of the present invention, the graphitization process includes using a graphitization furnace to graphitize the coke powder single particles or the shaped secondary particles.
[0041] As a technical solution of the present invention, the equipment used in the graphitization process is an Acheson graphitization furnace, a box-type graphitization furnace or a continuous graphitization furnace.
[0042] As a technical solution of the present invention, the temperature of the graphitization process is 2600-3200°C.
[0043] As a technical solution of the present invention, the single particle or the shaped secondary particle is cooled to room temperature at a cooling rate of 16 to 25° C. / min after graphitization to obtain the graphitized product.
[0044] As a technical solution of the present invention, the Dv50 of the graphitized product is 3 to 30 um.
[0045] As a technical solution of the present invention, the specific surface area of the graphitized product is 0.7 to 3.0 m 2 / g.
[0046] As a technical solution of the present invention, the tap density of the graphitized product is 0.9 to 1.4 g / cm 3 .
[0047] As a technical solution of the present invention, the graphitization is processed by a gradient temperature increase method.
[0048] As a technical solution of the present invention, the graphitization includes first heating the temperature to 2000-2500°C at a heating rate of 15-20°C / min, then heating the temperature to 3000-3200°C at a heating rate of 12-17°C / min, and keeping the temperature at 3000-3200°C for 3-4h.
[0049] As a technical solution of the present invention, the carbon coating agent accounts for 0.5-5.0% of the quality of the graphitized product.
[0050] As a technical solution of the present invention, the mixing equipment includes a fusion machine, a liquid phase mixer, a V-type mixer or a high-speed VC machine.
[0051] As a technical solution of the present invention, the mixing rotation speed is 50 to 1000 r / min.
[0052] As a technical solution of the present invention, the mixing time is 60 to 200 minutes.
[0053] As a technical solution of the present invention, the temperature of the carbonization process is 1000-1600°C.
[0054] As a technical solution of the present invention, the carbonization processing and heat preservation time is 2 to 10 hours.
[0055] As a technical solution of the present invention, the carbon coating agent includes at least one of petroleum asphalt, coal asphalt, natural asphalt, phenolic resin, epoxy resin, urea-formaldehyde resin, furfural phenol resin, furfuryl alcohol resin, polybutadiene resin, melamine formaldehyde resin, polyurethane, acrylic resin, lignin, starch, cellulose, sucrose and glucose.
[0056] As a technical solution of the present invention, the carbonization process is followed by back-end processing, and the back-end processing includes breaking up and screening.
[0057] As a technical solution of the present invention, the coke powder single particles can be obtained by coarsely crushing, pulverizing and shaping the raw coke, the coke powder single particles are subjected to a granulation process to obtain secondary particles, and the secondary particles are subjected to a shaping process to obtain the shaped secondary particles.
[0058] As a technical solution of the present invention, the coarse crushing includes crushing the green coke into particles with a diameter of 1 to 5 mm.
[0059] As a technical solution of the present invention, the pulverizing-shaping includes using pulverizing-shaping equipment to pulverize and shape single particles of coke powder with a Dv50 of 3 to 15 μm.
[0060] As a technical solution of the present invention, the granulation process includes using a granulation kettle to granulate to obtain secondary particles with a Dv50 of 10 to 35 μm.
[0061] As a technical solution of the present invention, the equipment of the granulation process is one of a drum furnace, a vertical granulation kettle, a horizontal granulation kettle and a continuous granulation kettle.
[0062] As a technical solution of the present invention, the temperature of the granulation step is 550°C to 750°C.
[0063] As a technical solution of the present invention, the shaping process includes using shaping equipment to shape the surface until Dv50 is 10 to 33 μm.
[0064] As a technical solution of the present invention, before the coking reaction, the carbon source and the small molecule nucleating agent are mixed and homogenized before the coking reaction.
[0065] As a technical solution of the present invention, the homogenized material is pumped into a heating furnace through a centrifugal pump for heating, and then flows into a coking tower heating furnace for the coking reaction.
[0066] As a technical solution of the present invention, the heating reaction time is 2 to 20 seconds, and the heating reaction temperature is 450 to 600°C.
[0067] The third aspect of the present invention provides a secondary battery, comprising a positive electrode material, a negative electrode material and an electrolyte. The negative electrode material comprises the aforementioned graphite negative electrode material, or a graphite negative electrode material prepared by the aforementioned method for preparing the graphite negative electrode material. BRIEF DESCRIPTION OF THE DRAWINGS
[0068] Figure 1 A schematic diagram of the interquartile range.
[0069] Figure 2 This is a diagram of the conventional polarization structure of the focus. DETAILED DESCRIPTION
[0070] The graphite negative electrode material of the present invention has the common properties of conventional graphite and is widely used, and is particularly suitable for use as a negative electrode material of a secondary battery. The secondary battery comprises a positive electrode material, a negative electrode material and an electrolyte.
[0071] The positive electrode material may be a layered transition metal lithium oxide or an olivine-type lithium compound. The layered transition metal lithium oxide may be, but is not limited to, lithium cobalt oxide (such as LiCoO2), lithium nickel oxide (such as LiNiO2), lithium manganese oxide (such as LiMnO2, LiMn2O4), lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide (chemical formula LiNi x Co y Mn (1-x-y) M z O2, wherein 0.6≤x<0.9, x+y<1, 0≤z<0.08, M is at least one of Al, Mg, Zr and Ti) and coatings and dopants of the above materials. Olivine-type lithium compounds are lithium-containing phosphates with an olivine structure, which may be, but are not limited to, lithium iron phosphate, lithium manganese phosphate, lithium manganese iron phosphate and coatings and dopants of the above materials. These positive electrode active materials may be used alone or in combination of two or more. Of course, the positive electrode materials of the present invention are not limited to the positive electrode materials listed above, and other positive electrode materials that can be used for lithium ion deintercalation are also possible.
[0072] The electrolyte includes an electrolyte salt, a non-aqueous organic solvent and an additive. The electrolyte salt may be, but is not limited to, at least one of lithium hexafluorophosphate (LiPF6), lithium perchlorate (LiClO4), lithium tetrafluoroborate (LiBF4), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethylsulfonyl)imide (LiTFSI), lithium methanesulfonate (LiCH3SO3), lithium trifluoromethylsulfonate (LiCF3SO3), lithium bis(oxalate)borate (C4BLiO8), lithium difluorooxalate borate (C2BF2LiO4), lithium difluorophosphate (LiPO2F2) and lithium difluorobis(oxalate)phosphate (LiDFBP). The non-aqueous organic solvent is selected from carbonates and / or carboxylates. Further, the non-aqueous organic solvent is selected from at least one of ethylene carbonate (PC), propylene carbonate (PC), dimethyl carbonate (DMC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC), γ-butyrolactone, methyl acetate, ethyl acetate, propyl acetate, butyl acetate, ethyl propionate, propyl propionate and butyl propionate. Additives may include ethylene carbonate (VC), vinylene carbonate (VEC), fluoroethylene carbonate (FEC), vinyl sulfate (ES), propane sulfonate (PS), etc. Of course, the electrolyte of the present invention is not limited to the combination of the electrolyte salt, non-aqueous organic solvent and additive listed above, and other electrolytes that can shuttle lithium ions are also possible.
[0073] The graphite negative electrode material of the present invention is tested by Raman and meets the conditions of AD / AG≥1.0 and IQR≤0.25. As an example, AD / AG can be, but not limited to, 1.0, 1.2, 1.4, 1.6, 1.8, 2.0, 2.2, 2.4, 2.6, 2.8, 3.0. IQR can be, but not limited to, 0.25, 0.23, 0.21, 0.20, 0.18, 0.16, 0.14, 0.12, 0.10. Among them, AD / AG is the peak area ratio of the D peak and the G peak in the spectrum of the Raman test, IQR is the interquartile range of AD / AG, and the D peak is located at a wavelength of 1350cm -1 The defect peak is caused by the defects of graphite crystal plane, heteroatoms or edge effects. The G peak is located at a wavelength of 1580cm -1 The ideal graphite crystal characteristic peak. In the spectrum, AD / AG≥1.0, IQR≤0.25, indicating that the amorphous carbon outer layer of the graphite negative electrode material is evenly coated. Raman testing can be performed using the XploRA PLUS Raman spectrometer equipment of HORIBA manufacturer, and the test is performed at ≤50 points. In addition, the calculation method of the interquartile range of AD / AG can refer to Figure 1 , the interquartile range is the difference between the third quartile and the first quartile.
[0074] The specific surface area of graphite negative electrode material is 0.5~2.0m 2 / g, as an example, it can be but not limited to 0.5m 2 / g, 0.6m 2 / g, 0.7m 2 / g, 0.8m 2 / g, 0.9m 2 / g, 1.0m 2 / g, 1.1m 2 / g, 1.2m 2 / g, 1.3m 2 / g, 1.4m 2 / g, 1.5m 2 / g, 1.6m 2 / g, 1.7m 2 / g, 1.8m 2 / g, 1.9m 2 / g, 2.0m 2 / g. The tap density of graphite negative electrode material is 0.9~1.4g / cm 3 , as an example, it can be but not limited to 0.9 g / cm 3 , 1.0g / cm 3 , 1.1g / cm 3 , 1.2g / cm 3 , 1.3g / cm 3 , 1.4 / cm3 The Dv50 of the graphite negative electrode material is 3 to 30 μm, and as an example, it can be, but not limited to, 3 μm, 5 μm, 10 μm, 15 μm, 20 μm, 25 μm, and 30 μm. The interlayer spacing d002 of the graphite negative electrode material is 0.3355 to 0.3400 nm, and as an example, it can be, but not limited to, 0.3355 nm, 0.3360 nm, 0.3365 nm, 0.3370 nm, 0.3375 nm, 0.3380 nm, 0.3385 nm, 0.3390 nm, 0.3395 nm, and 0.3400 nm. The degree of graphitization of the graphite negative electrode material is 85-97%. As an example, it can be but not limited to 85%, 86%, 87%, 88%, 89%, 90%, 91%, 92%, 93%, 94%, 95%, 96%, and 97%.
[0075] The 0.1C first charge capacity of the graphite negative electrode material is ≥320mAh / g. As an example, it can be, but not limited to, ≥320mAh / g, ≥330mAh / g, ≥340mAh / g, ≥350mAh / g, ≥355mAh / g, ≥360mAh / g, ≥365mAh / g, ≥370mAh / g, ≥375mAh / g, ≥380mAh / g, ≥385mAh / g, ≥390mAh / g. The 0.1C first charge and discharge efficiency of the graphite negative electrode material is ≥90%. As an example, it can be, but not limited to, ≥90%, ≥91%, ≥92%, ≥93%, ≥94%, ≥95%. The capacity retention rate of the graphite negative electrode material at 1.0C / 0.1C is ≥70%. As an example, it can be, but not limited to, ≥70%, ≥71%, ≥72%, ≥73%, ≥74%, ≥75%, ≥76%, ≥77%, ≥78%, ≥79%, ≥80%. The capacity retention rate of the graphite negative electrode material at 2.0C / 0.1C is ≥55%. As an example, it can be, but not limited to, ≥55%, ≥56%, ≥57%, ≥58%, ≥59%, ≥60%, ≥61%, ≥62%, ≥63%, ≥64%, ≥65%, ≥66%, ≥67%, ≥68%, ≥69%. The 3.0C / 0.1C capacity retention rate of the graphite negative electrode material is ≥35%. As an example, it can be but not limited to ≥35%, ≥36%, ≥37%, ≥38%, ≥39%, ≥40%, ≥41%, ≥42%, ≥43%, ≥44%, and ≥45%.
[0076] The graphite negative electrode material of the present invention comprises a graphite core and an amorphous carbon outer layer. The graphite core is artificial graphite. Alternatively, the graphite core comprises artificial graphite single particles and / or artificial graphite secondary particles. The single particles are the initial particles formed during the processing of the graphite raw materials, and there are no structures such as stacking and flocculation in the powder particles. The graphite secondary particles are particles that are formed by processing again on the basis of the graphite single particles and undergo a certain degree of agglomeration and bonding. As a technical solution of the present invention, the graphite core can be obtained by coking coal tar or oil slurry and then graphitizing it. The amorphous carbon outer layer can be obtained by carbonizing a carbon source, which can be one layer or more layers. The amorphous carbon outer layer is evenly distributed on the surface of the graphite core and / or dispersed between the graphite core particles, and exists in the form of a uniform coating. The thickness of the amorphous carbon outer layer is 5 to 500 nm, and as examples, may be, but is not limited to, 5 nm, 50 nm, 100 nm, 150 nm, 200 nm, 250 nm, 300 nm, 350 nm, 400 nm, 450 nm, and 500 nm.
[0077] The preparation method of the graphite negative electrode material of the present invention comprises the following steps: 1. adding a small molecule nucleating agent to a carbon source, and then subjecting the carbon source to a coking reaction to obtain raw coke; 2. subjecting the raw coke to a front-end processing step to obtain a coke powder single particle or a shaped secondary particle, wherein the front-end processing step comprises at least one of a crushing step, a shaping step, a granulation step and a secondary shaping step; 3. subjecting the coke powder single particle or the shaped secondary particle to a graphitized product by graphitization processing; and 4. mixing the graphitized product with a carbon coating agent and subjecting the mixture to a carbonization processing to obtain a carbonized product.
[0078] Optical tissue detection of the raw foci was performed, and according to the morphological characteristics and isochromatic zone size of the raw foci under a polarizing microscope, such as Figure 2As shown, its optical structure can be divided into three categories: mosaic structure (Figure a), regional structure (Figure b, Figure c) and fiber structure (Figure d). These classifications mainly depend on the generation, growth, fusion and disintegration deformation of the intermediate phase spheres during the coking process. Among them, the mosaic structure is represented by a small medium color area size (<30μm) in the polarization image of the optical organization. This structure has a poor degree of preferential orientation and presents a certain degree of anisotropy. The regional structure is represented by a structure with a medium color area size of 30 to 100μm in the polarization image of the optical organization. The degree of preferential orientation changes from weak to medium. According to the size of the isochromatic area, it can be subdivided into two small categories: small domain structure (Figure b) and large domain structure (Figure c). The small domain structure is a structure with a medium color area size of 30 to 50μm in the polarization image of the optical organization. The large domain structure is a structure with a medium color area size of 50 to 100μm in the polarization image of the optical organization. The fiber-type structure has a clear preferential orientation. According to the size of the medium color zone in the polarized image of the optical organization, it can be subdivided into three categories: short fiber, medium fiber and long fiber. The size of the strip-shaped isochromatic zone of the short fiber microstructure is less than 100μm. The size of the strip-shaped isochromatic zone of the medium fiber microstructure is 100-500μm. The size of the isochromatic zone of the long fiber microstructure is greater than 500μm. The optical organization can be tested using the Axioscope5 equipment of Beijing Puruiss Company, and the content of the mosaic structure and the small domain structure is obtained by using the coal rock analysis software ICPAS.
[0079] The raw coke of the mosaic structure and the small domain structure has the advantages of high softening point, high coking value and residual carbon rate, easy graphitization, etc., especially the microcrystals of graphite formed after high-temperature heat treatment are fine, the grain size is uniform, the structure is uniform, and the isotropy is high. The large domain structure and the fiber structure have a high degree of preferential orientation and few defects, which are conducive to the growth and development of microcrystals during graphitization. In addition, the high degree of graphitization is conducive to the capacity improvement of graphite negative electrode materials. Therefore, in order to improve the rate performance of the graphite negative electrode material while ensuring its capacity, it is necessary to control the content distribution of the mosaic structure, the small domain structure, the large domain structure and the fiber structure. The raw coke of the present invention meets the condition 1.2≤4×A+B<4.0 after optical tissue detection, wherein A and B represent the content of the mosaic structure and the small domain structure in the optical tissue, respectively. As an example, 4×A+B may be, but not limited to, 1.2, 1.5, 1.8, 2.0, 2.3, 2.6, 2.8, 3.0, 3.3, 3.5, 3.8, 3.9. As a technical solution of the present invention, A≥0.3, as an example, A may be, but not limited to, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9. B≥0.2, as an example, B may be, but not limited to, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9.
[0080] The carbon source is coal tar or oil slurry. Small molecule nucleating agents include graphite fine powder, graphitized coke fine powder, and transition metal fine powder. The particle size of the small molecule nucleating agent is ≤50μm. As an example, the particle size can be but not limited to 5μm, 10μm, 15μm, 20μm, 25μm, 30μm, 35μm, 40μm, 45μm, and 50μm. Graphitized coke fine powder refers to graphitized needle coke, petroleum coke, coal-based coke and other fine powders. Transition metal fine powder refers to a solid powder with transition metal as the main active component, which can be transition elements such as iron, cobalt, and nickel. As a non-uniform nucleation, the small molecule nucleating agent has a small nucleation volume and a small nucleation work, so the structural fluctuations and energy fluctuations required for nucleation are small, and it is easy to nucleate. After the two are mixed and homogenized, a small molecule nucleating agent can be used as a template, and the carbon source molecules diffuse and adsorb to the small molecule nucleating agent, and are easily nucleated and developed into an intermediate phase. After the coking reaction, raw coke with more mosaic structures and small domain structures can be obtained. The small molecule nucleating agent is 0.01-1.00% of the mass of the carbon source. As an example, it can be but not limited to 0.01%, 0.05%, 0.10%, 0.20%, 0.30%, 0.40.0%, 0.50%, 0.60%, 0.70%, 0.80%, 0.90%, 1.00%. The content of the small molecule nucleating agent needs to be strictly controlled. The more its content, the more heterogeneous nucleation units, and the more mosaic structures or small domain structures of raw coke may be obtained. Conversely, the more large domain structures or fiber structures may be obtained in the raw coke.
[0081] The carbon source and the small molecule nucleating agent are mixed evenly, that is, after the two are homogenized, the homogenized material can be subjected to a coking reaction. Further, the homogenized material is pumped into a heating furnace for heating via a centrifugal pump, and then flows into a coking tower for a coking reaction. The heating reaction time is 2 to 20 seconds, and as an example, it can be but not limited to 2 seconds, 4 seconds, 6 seconds, 8 seconds, 10 seconds, 12 seconds, 14 seconds, 16 seconds, 18 seconds, 20 seconds, 22 seconds, 24 seconds, 26 seconds, 28 seconds, and 30 seconds. The heating reaction temperature is 450 to 600 degrees Celsius, and as an example, it can be but not limited to 450 degrees Celsius, 460 degrees Celsius, 470 degrees Celsius, 480 degrees Celsius, 490 degrees Celsius, 500 degrees Celsius, 510 degrees Celsius, 520 degrees Celsius, 530 degrees Celsius, 540 degrees Celsius, 550 degrees Celsius, 580 degrees Celsius, and 600 degrees Celsius. The coking reaction is carried out in a coking tower, and the pressure of the coking tower is 50-700KPa, and as an example, it can be, but not limited to, 50KPa, 100KPa, 150KPa, 200KPa, 250KPa, 300KPa, 350KPa, 400KPa, 450KPa, 500KPa, 550KPa, 600KPa, 650KPa, 700KPa. The coking time is 8-30h, and as an example, it can be, but not limited to, 8h, 10h, 12h, 14h, 16h, 18h, 20h, 22h, 24h, 26h, 28h, 30h.
[0082] In step ②, the single particles of coke powder can be obtained by coarse crushing and crushing-shaping of raw coke. The single particles of coke powder are subjected to a granulation process to obtain secondary particles, and the secondary particles are subjected to a shaping process to obtain raw rubber shaped secondary particles. Coarse crushing includes crushing the raw coke to a particle size of 1 to 5 mm, as an example, it can be but not limited to 1mm, 2mm, 3mm, 4mm, 5mm. Crushing-shaping includes using a crushing-shaping device to crush-shaping to obtain single particles of coke powder with a Dv50 of 3 to 15μm. As an example, Dv50 can be but not limited to 7μm, 9μm, 11μm, 13μm, 15μm, 17μm, 19μm, 20μm. The granulation process includes using a granulation kettle to granulate to obtain secondary particles with a Dv50 of 10 to 35μm. As an example, Dv50 can be but not limited to 10μm, 15μm, 20μm, 25μm, 30μm, 35μm. The equipment of the granulation process includes a drum furnace, a vertical granulation kettle, a horizontal granulation kettle or a continuous granulation kettle. The temperature of the granulation process is 550°C to 750°C. As an example, it can be but not limited to 550°C, 600°C, 650°C, 700°C, and 750°C. The shaping process includes shaping to Dv50 of 10 to 33μm using shaping equipment. As an example, Dv50 can be but not limited to 10Dv50 is 10μm, 15μm, 20μm, 25μm, 30μm, and 33μm.
[0083] In step ③, the graphitization process includes graphitizing single particles of coke powder or shaped secondary particles using a graphitization furnace. The equipment used for the graphitization process is an Acheson graphitization furnace, a box-type graphitization furnace or a continuous graphitization furnace. The temperature of the graphitization process is 2600-3200°C. As an example, the temperature can be, but is not limited to, 2600°C, 2650°C, 2700°C, 2750°C, 2800°C, 2850°C, 2900°C, 2950°C, 3000°C, 3050°C, 3100°C, 3150°C, 3200°C. Graphitization is carried out by gradient heating. Furthermore, graphitization includes first heating to 2000-2500°C at a heating rate of 15-20°C / min, then heating to 3000-3200°C at a heating rate of 12-17°C / min, and keeping at 3000-3200°C for 3-4h. After graphitization, the graphitized product is obtained by cooling to room temperature at a cooling rate of 16-25°C / min. The Dv50 of the graphitized product is 3-30um. As an example, it can be but not limited to 3μm, 5μm, 10μm, 15μm, 20μm, 25μm, and 30μm. The specific surface area of the graphitized product is 0.7-3.0m 2 / g, as an example, it can be but not limited to 0.7g / cm 2 , 1.0g / cm 2 , 1.5g / cm 2 , 2.0g / cm2 , 2.5g / cm 2 、3.0g / cm 2 The tap density of graphitized products is 0.9~1.4g / cm 3 , as an example, it can be but not limited to 0.9 g / cm 3 , 1.0g / cm 3 , 1.1g / cm 3 , 1.2g / cm 3 , 1.3g / cm 3 , 1.4g / cm 3 .
[0084] In step ④, the carbon coating agent includes at least one of petroleum asphalt, coal asphalt, natural asphalt, phenolic resin, epoxy resin, urea-formaldehyde resin, furfural phenol resin, furfuryl alcohol resin, polybutadiene resin, melamine formaldehyde resin, polyurethane, acrylic resin, lignin, starch, cellulose, sucrose and glucose. The carbon coating agent accounts for 0.5-5.0% of the quality of the graphitized product. As an example, it can be but not limited to 0.5%, 1.0%, 1.5%, 2.0%, 2.5%, 3.0%, 3.5%, 4.0%, 4.5%, 5.0%. The equipment for mixing the graphitized product and the carbon coating agent includes a fusion machine, a liquid phase mixer, a V-type mixer or a high-speed VC machine. The mixing speed is 50-1000r / min. As an example, the speed can be, but not limited to, 50r / min, 100r / min, 200r / min, 300r / min, 400r / min, 500r / min, 600r / min, 700r / min, 800r / min, 900r / min, 1000r / min. The mixing time is 60-200min. As an example, it can be, but not limited to, 60min, 80min, 100min, 120min, 140min, 160min, 180min, 200min. The temperature of the carbonization process is 1000-1600℃. As an example, it can be, but not limited to, 1000℃, 1100℃, 1200℃, 1300℃, 1400℃, 1500℃, 1600℃. The heat preservation time of carbonization processing is 2 to 10 hours, for example, it can be but not limited to 4 hours, 6 hours, 8 hours, 10 hours, 12 hours, 14 hours, 16 hours. Through the regulation of coating equipment and its parameters, the adjustment of carbon coating parameters (such as coating temperature, coating amount, different coating agents, etc.) to form a uniform carbon coating layer. After carbonization processing, the back-end processing is carried out, and the back-end processing includes breaking up and screening.
[0085] The graphite negative electrode material obtained after carbonization meets the conditions of AD / AG≥1.0 and IQR≤0.25 after Raman testing, where AD / AG is the peak area ratio of the D peak and the G peak in the spectrum of the Raman test, IQR is the interquartile range of AD / AG, and the D peak is located at a wavelength of 1350cm -1 The defect peak of G peak is located at a wavelength of 1580cm -1 As an example, AD / AG may be, but is not limited to, 1.0, 1.2, 1.4, 1.6, 1.8, 2.0, 2.2, 2.4, 2.6, 2.8, 3.0. IQR may be, but is not limited to, 0.25, 0.23, 0.21, 0.20, 0.18, 0.16, 0.14, 0.12, 0.10.
[0086] In order to better illustrate the purpose, technical scheme and beneficial effects of the present invention, the present invention will be further described below in conjunction with specific embodiments. It should be noted that the following implementation method is a further explanation of the present invention and should not be used as a limitation of the present invention.
[0087] Example 1
[0088] This embodiment is a method for preparing a graphite negative electrode material, which includes the following steps.
[0089] ① Take refined coal tar as raw material, add graphite fine powder (particle size is about 20μm) accounting for 0.6wt.% of refined coal tar, mix the two and homogenize them, then pump them into the heating furnace through a centrifugal pump and stay for 10s before entering the coking tower. The heating furnace temperature is 520℃, the pressure of the coking tower is 200~250KPa, the coking time is 12h, and the raw coke is obtained by cooling at room temperature after coking.
[0090] ② The raw coke is coarsely broken and pulverized to a particle size of 2 to 3 mm, and then pulverized and shaped by a pulverizing-shaping device to obtain single coke powder particles with a Dv50 of 3 to 15 μm.
[0091] ③ The coke powder single particles are granulated in a drum furnace to obtain secondary particles with a Dv50 of 10 to 35 μm, and the granulation temperature is set to 650°C.
[0092] ④ The secondary particles are shaped by shaping equipment to a Dv50 of 10 to 33 μm to obtain shaped secondary particles.
[0093] ⑤ The shaped secondary particles are subjected to high-temperature graphitization treatment in a continuous graphitization furnace, specifically, the temperature is raised to 2300°C at a heating rate of 18°C / min, and then the temperature is raised to 3000°C at a heating rate of 15°C / min and kept at this temperature for 3 hours. After the graphitization treatment, the graphitized product is obtained by cooling to room temperature at a cooling rate of 20°C / min.
[0094] ⑥ The graphitized product and phenolic resin (accounting for 4% of the quality of the graphitized product) were stirred and mixed in a liquid phase mixer at a speed of 600r / min for 120min. After stirring, the mixture was carbonized in a nitrogen atmosphere at 1150°C for 10h, and finally the graphite negative electrode material was obtained after being broken up and sieved.
[0095] Example 2
[0096] This embodiment is a method for preparing a graphite negative electrode material, which includes the following steps.
[0097] ① Take oil slurry as raw material, add graphite fine powder (particle size is about 20μm) accounting for 0.8wt.% of the oil slurry, mix the two and homogenize them, then pump them into the heating furnace by centrifugal pump, stay for 10s and then enter the coking tower. The heating furnace temperature is 520℃, the pressure of the coking tower is 550-650KPa, the coking time is 10h, and the raw coke is obtained by cooling at room temperature after coking.
[0098] ② The raw coke is roughly crushed to a particle size of 2 to 3 mm, and then crushed and shaped by a crushing-shaping equipment to obtain single coke powder particles with a Dv50 of 3 to 15 μm.
[0099] ③ The coke powder single particles are granulated in a drum furnace to obtain secondary particles with a Dv50 of 10 to 35 μm, and the granulation temperature is set to 650°C.
[0100] ④ The secondary particles are shaped by shaping equipment to a Dv50 of 10 to 33 μm to obtain shaped secondary particles.
[0101] ⑤ The shaped secondary particles are subjected to high-temperature graphitization treatment in a continuous graphitization furnace, specifically, the temperature is raised to 2300°C at a heating rate of 18°C / min, and then the temperature is raised to 3000°C at a heating rate of 15°C / min and kept at this temperature for 3 hours. After the graphitization treatment, the graphitized product is obtained by cooling to room temperature at a cooling rate of 20°C / min.
[0102] ⑥ The graphitized product and phenolic resin (accounting for 5% of the quality of the graphitized product) are stirred and mixed in a liquid phase mixer at a speed of 400r / min for 90min. After stirring, carbonization is performed in a nitrogen atmosphere at 1150°C for 10h, and finally the graphite negative electrode material is obtained after being broken up and screened.
[0103] Example 3
[0104] This embodiment is a method for preparing a graphite negative electrode material, which includes the following steps.
[0105] ① Take refined coal tar as raw material, add graphite fine powder (particle size is about 20μm) accounting for 0.4wt.% of refined coal tar, mix and homogenize the two, inject into the heating furnace through the gear pump, stay for 10s and then enter the coking tower. The heating furnace temperature is 520℃, the pressure of the coking tower is 200~250KPa, the coking time is 12h, and the raw coke is obtained by cooling at room temperature after coking.
[0106] ② The raw coke is coarsely broken and pulverized to a particle size of 2 to 3 mm, and then pulverized and shaped by a pulverizing-shaping device to obtain single coke powder particles with a Dv50 of 3 to 15 μm.
[0107] ③ The coke powder single particles are granulated in a drum furnace to obtain secondary particles with a Dv50 of 10 to 35 μm, and the granulation temperature is set to 650°C.
[0108] ④ The secondary particles are shaped by shaping equipment to a Dv50 of 10 to 33 μm to obtain shaped secondary particles.
[0109] ⑤ The shaped secondary particles are subjected to high-temperature graphitization treatment in a continuous graphitization furnace, specifically, the temperature is raised to 2300°C at a heating rate of 18°C / min, and then the temperature is raised to 3000°C at a heating rate of 15°C / min and kept at this temperature for 3 hours. After the graphitization treatment, the graphitized product is obtained by cooling to room temperature at a cooling rate of 20°C / min.
[0110] ⑥ The graphitized product and asphalt (accounting for 3% of the quality of the graphitized product, the asphalt softening point is 180°C, and crushed into small micron-sized particles with a Dv50 of 4 to 8 μm before use) are stirred and mixed in a fusion machine at a speed of 600 r / min for 90 minutes. After stirring, carbonization is performed at 1150°C in a nitrogen atmosphere for 10 hours, and finally the graphite negative electrode material is obtained after being broken up and screened.
[0111] Example 4
[0112] This embodiment is a method for preparing a graphite negative electrode material, which includes the following steps.
[0113] ① Take refined coal tar as raw material, add graphite fine powder (particle size is about 20μm) accounting for 0.7wt.% of refined coal tar, mix and homogenize them, then pump them into the heating furnace by centrifugal pump, stay for 10s and then enter the coking tower. The heating furnace temperature is 520℃, the pressure of the coking tower is 200~250KPa, the coking time is 12h, and the raw coke is obtained by cooling at room temperature after coking.
[0114] ② The raw coke is roughly crushed to a particle size of 2 to 3 mm, and then crushed and shaped by a crushing-shaping equipment to obtain single coke powder particles with a Dv50 of 3 to 15 μm.
[0115] ③ The coke powder single particles are granulated in a horizontal granulation kettle to obtain secondary particles with a Dv50 of 10 to 35 μm, and the granulation temperature is set at 550°C;
[0116] ④ The secondary particles are shaped by shaping equipment to a Dv50 of 10 to 33 μm to obtain shaped secondary particles;
[0117] ⑤ The shaped secondary particles are subjected to high-temperature graphitization treatment in a continuous graphitization furnace, specifically, the temperature is raised to 2300°C at a heating rate of 18°C / min, and then the temperature is raised to 3000°C at a heating rate of 15°C / min and kept at this temperature for 3 hours. After the graphitization treatment, the graphitized product is obtained by cooling to room temperature at a cooling rate of 20°C / min.
[0118] ⑥ The graphitized product and phenolic resin (accounting for 4% of the quality of the graphitized product) were stirred and mixed in a liquid phase mixer at a speed of 600r / min for 120min. After stirring, the mixture was carbonized in a nitrogen atmosphere at 1150°C for 10h, and finally the graphite negative electrode material was obtained after being broken up and sieved.
[0119] Example 5
[0120] This embodiment is a method for preparing a graphite negative electrode material, which includes the following steps.
[0121] ① Take refined coal tar as raw material, add graphite fine powder (particle size is about 20μm) accounting for 1.00wt.% of refined coal tar, mix the two and homogenize them, then pump them into the heating furnace through a centrifugal pump and stay for 10s before entering the coking tower. The heating furnace temperature is 520℃, the pressure of the coking tower is 200~250KPa, the coking time is 12h, and the raw coke is obtained by cooling at room temperature after coking.
[0122] ② The raw coke is roughly crushed to a particle size of 2 to 3 mm, and then crushed and shaped by a crushing-shaping equipment to obtain single coke powder particles with a Dv50 of 3 to 15 μm.
[0123] ③ The coke powder single particles are granulated in a drum furnace to obtain secondary particles with a Dv50 of 10 to 35 μm, and the granulation temperature is set to 650°C.
[0124] ④ The secondary particles are shaped by shaping equipment to a Dv50 of 10 to 33 μm to obtain shaped secondary particles.
[0125] ⑤ The shaped secondary particles are subjected to high-temperature graphitization treatment in a continuous graphitization furnace, specifically, the temperature is raised to 2300°C at a heating rate of 18°C / min, and then the temperature is raised to 3000°C at a heating rate of 15°C / min and kept at this temperature for 3 hours. After the graphitization treatment, the graphitized product is obtained by cooling to room temperature at a cooling rate of 20°C / min.
[0126] ⑥ The graphitized product and phenolic resin (accounting for 4% of the quality of the graphitized product) were stirred and mixed in a liquid phase mixer at a speed of 600r / min for 120min. After stirring, the mixture was carbonized in a nitrogen atmosphere at 1150°C for 10h, and finally the graphite negative electrode material was obtained after being broken up and sieved.
[0127] Example 6
[0128] This embodiment is a method for preparing a graphite negative electrode material, which includes the following steps.
[0129] ① Take refined coal tar as raw material, add 0.6wt.% of graphitizable coke fine powder (particle size is about 30μm), mix and homogenize the two, add them into the heating furnace through a centrifugal pump, stay for 10s and then enter the coking tower. The heating furnace temperature is 520℃, the pressure of the coking tower is 200-250KPa, the coking time is 10h, and the green coke is obtained by cooling at room temperature after coking.
[0130] ② The raw coke is roughly crushed to a particle size of 4 to 5 mm, and then crushed and shaped by a crushing-shaping equipment to obtain single coke powder particles with a Dv50 of 8 to 15 μm.
[0131] ③ The single particle of coke powder is subjected to high-temperature graphitization treatment in a continuous graphitization furnace, specifically, the temperature is increased to 2300°C at a heating rate of 18°C / min, and then the temperature is increased to 3000°C at a heating rate of 15°C / min and kept at this temperature for 3 hours. After the graphitization treatment, the single particle is cooled to room temperature at a cooling rate of 20°C / min to obtain a graphitized product.
[0132] ④ The graphitized product and phenolic resin (accounting for 4% of the quality of the graphitized product) were stirred and mixed in a liquid phase mixer at a speed of 600r / min for 120min. After stirring, the mixture was carbonized in a nitrogen atmosphere at 1150°C for 10h, and finally the graphite negative electrode material was obtained after being broken up and sieved.
[0133] Example 7
[0134] This embodiment is a method for preparing a graphite negative electrode material, which includes the following steps.
[0135] ① Take refined coal tar as raw material, add graphite fine powder (particle size is about 20μm) accounting for 0.6wt.% of refined coal tar, mix the two and homogenize them, then pump them into the heating furnace through a centrifugal pump and stay for 10s before entering the coking tower. The heating furnace temperature is 520℃, the pressure of the coking tower is 200~250KPa, the coking time is 12h, and the raw coke is obtained by cooling at room temperature after coking.
[0136] ② The raw coke is roughly crushed to a particle size of 2 to 3 mm, and then crushed and shaped by a crushing-shaping equipment to obtain single coke powder particles with a Dv50 of 3 to 15 μm.
[0137] ③ The single particle of coke powder is subjected to high-temperature graphitization treatment in a continuous graphitization furnace, specifically, the temperature is increased to 2400°C at a heating rate of 20°C / min, and then the temperature is increased to 3200°C at a heating rate of 16°C / min and kept at this temperature for 4 hours. After the graphitization treatment, the single particle is cooled to room temperature at a cooling rate of 25°C / min to obtain a graphitized product.
[0138] ④ The graphitized product and phenolic resin (accounting for 3% of the quality of the graphitized product) were stirred and mixed in a liquid phase mixer at a speed of 800r / min for 100min. After stirring, the mixture was carbonized in a nitrogen atmosphere at 1000°C for 12h, and finally the graphite negative electrode material was obtained after being broken up and sieved.
[0139] Example 8
[0140] This embodiment is a method for preparing a graphite negative electrode material, which includes the following steps.
[0141] ① Take refined coal tar as raw material, add graphite fine powder (particle size is about 20μm) accounting for 0.6wt.% of refined coal tar, mix the two and homogenize them, then pump them into the heating furnace through a centrifugal pump and stay for 10s before entering the coking tower. The heating furnace temperature is 520℃, the pressure of the coking tower is 200~250KPa, the coking time is 12h, and the raw coke is obtained by cooling at room temperature after coking.
[0142] ② The raw coke is coarsely broken and pulverized to a particle size of 2 to 3 mm, and then shaped and pulverized by a shaping and pulverizing-shaping equipment to obtain single coke powder particles with a Dv50 of 3 to 15 μm.
[0143] ③ The coke powder single particles are granulated in a drum furnace to obtain secondary particles with a Dv50 of 10 to 35 μm, and the granulation temperature is set to 650°C.
[0144] ④ The secondary particles are shaped by shaping equipment to a Dv50 of 10 to 33 μm to obtain shaped secondary particles.
[0145] ⑤ The shaped secondary particles are subjected to high-temperature graphitization treatment in a continuous graphitization furnace, specifically, the temperature is raised to 3000°C at a heating rate of 18°C / min and kept at this temperature for 3 hours. After the graphitization treatment, the particles are cooled to room temperature at a cooling rate of 20°C / min to obtain a graphitized product.
[0146] ⑥ The graphitized product and phenolic resin (accounting for 4% of the quality of the graphitized product) are stirred and mixed in a fusion machine at a speed of 600r / min for 120min. After stirring, carbonization is performed in a nitrogen atmosphere at 1150°C for 10h, and finally the graphite negative electrode material is obtained after being broken up and screened.
[0147] Comparative Example 1
[0148] This comparative example is a method for preparing a graphite negative electrode material, which includes the following steps.
[0149] ① Take refined coal tar as raw material, inject it into the heating furnace through gear pump, stay for 10s and then enter the coking tower. The temperature of the heating furnace is 520℃, the pressure of the coking tower is 200~250KPa, the coking time is 12h, and the raw coke is obtained by cooling at room temperature after coking.
[0150] ② The raw coke is roughly crushed to a particle size of 2 to 3 mm, and then crushed and shaped by a crushing-shaping equipment to obtain single coke powder particles with a Dv50 of 3 to 15 μm.
[0151] ③ The single particle of coke powder is subjected to high temperature graphitization treatment in a continuous graphitization furnace, specifically at 18°C
[0152] The temperature was raised to 2300°C at a heating rate of 15°C / min, and then raised to 3000°C at a heating rate of 15°C / min and kept at this temperature for 3 hours. After graphitization, the temperature was cooled to room temperature at a cooling rate of 20°C / min to obtain a graphite negative electrode material.
[0153] Comparative Example 2
[0154] This comparative example is a method for preparing a graphite negative electrode material, which includes the following steps.
[0155] ① Take refined coal tar as raw material, add it into the heating furnace through a centrifugal pump, stay for 10 seconds and then enter the coking tower. The temperature of the heating furnace is 520℃, the pressure of the coking tower is 200~250KPa, the coking time is 12h, and the green coke is obtained by cooling at room temperature after coking.
[0156] ② The raw coke is roughly crushed to a particle size of 2 to 3 mm, and then crushed and shaped by a crushing-shaping equipment to obtain single coke powder particles with a Dv50 of 3 to 15 μm.
[0157] ③ The single particle of coke powder is subjected to high-temperature graphitization treatment in a continuous graphitization furnace, specifically, the temperature is increased to 2300°C at a heating rate of 18°C / min, and then the temperature is increased to 3000°C at a heating rate of 15°C / min and kept at this temperature for 3 hours. After the graphitization treatment, the single particle is cooled to room temperature at a cooling rate of 20°C / min to obtain a graphitized product.
[0158] ④ The graphitized product and phenolic resin (accounting for 4% of the quality of the graphitized product) were stirred and mixed in a V-type mixer at a speed of 600r / min for 120min. After stirring, the mixture was carbonized in a nitrogen atmosphere at 1150°C for 10h, and finally the graphite negative electrode material was obtained after being broken up and sieved.
[0159] The raw coke in step ① of Examples 1 to 8 and Comparative Examples 1 to 2 was tested using Axioscope5 equipment from Beijing Puruiss Company, and the contents of the mosaic structure and the small domain structure (A, B) were statistically obtained using coal rock analysis software ICPAS. The graphite negative electrode materials prepared in Examples 1 to 8 and Comparative Examples 1 to 2 were subjected to various performance tests, and the test results are shown in Table 1, and the test methods are shown below.
[0160] Raman test: HORIBA's XploRAPLUS Raman spectrometer was used to test 20 points. AD / AG and IQR were calculated based on the spectrum, and the average value was taken after removing the outliers.
[0161] Particle size test: Malvern laser particle size analyzer MS2000 was used for testing.
[0162] Specific surface area test: measured using a Quantachrome surface area tester, NOVA2000e.
[0163] Thickness test of amorphous carbon outer layer: measured by photographing multiple particle cross-section morphologies using a JEOL field emission scanning electron microscope TSM-7900F.
[0164] Tap density test: The test was carried out using Dandong Better BT-302 tap density tester.
[0165] Interlayer spacing d002: The 002 and 100 diffraction peak patterns of graphite were automatically recorded using a Malvern Panalytical X-ray diffractometer. The diffraction angle was read simultaneously and the diffraction angle (2θcor) corrected for silicon powder was obtained by the internal standard method. The interlayer spacing d002 of graphite was calculated based on the Bragg formula d002 = λ / 2sin(θcor(002)).
[0166] Graphitization degree: The graphitization degree is calculated from the interlayer spacing d002 according to Franklin's formula.
[0167] Graphitization degree = (0.3440-d002) / (0.3440-0.3354)*100%,
[0168] 0.3440 represents the interlayer spacing of completely ungraphitized carbon, and the unit is nm.
[0169] 0.3354 represents the interlayer spacing of ideal graphite, and the unit is nm.
[0170] Half-cell electrical performance test: N-methylpyrrolidone is used as solvent to prepare a polyvinylidene fluoride solution with a mass fraction of 6-7%, and the graphite negative electrode material, polyvinylidene fluoride, and conductive carbon black prepared in Examples 1-8 and Comparative Examples 1-2 are mixed uniformly with N-methylpyrrolidone in a mass ratio of 91:7:2 to obtain a slurry with a solid content of 40%. The slurry is applied to a copper foil to obtain a pole piece, and the coated pole piece is placed in a vacuum drying oven at a temperature of 110°C and vacuum dried for 4 hours for standby use, and then punched into a small disc with a diameter of 14 mm. Then it is transferred to an argon-filled glove box and assembled into a 2032-type button cell, and a three-component mixed solvent of 1 mol / L LiPF6 is mixed according to EC:DMC:EMC=1:1:1 (volume ratio), and vinylene carbonate (accounting for 1% of the mass of the electrolyte) is added to mix as an electrolyte, a metal lithium sheet is used as a counter electrode, and a Ube diaphragm is used as an isolation membrane. The assembled half-cell is tested for electrochemical performance on an electrochemical detection system. At room temperature, discharge at a constant current of 0.1C until the voltage reaches 0.01V, then discharge at a constant current of 0.02C until the voltage reaches 0.005V, and charge at a constant current of 0.1C until the voltage reaches 1.5V. The capacity charged to 1.5V is the first charge capacity of 0.1C, and the ratio of the first charge capacity to the first discharge capacity is the first coulomb efficiency. After 2 weeks of 0.1C charging and 0.1C discharge cycles, constant current and constant voltage charging is performed at a rate of 1.0C (cutoff condition is 0.01C), followed by 1.0C constant current discharge. After three weeks of cycling at a rate of 1.0C, the reversible capacity at the rate of 1.0C is recorded and compared with the reversible capacity at 0.1C to obtain the capacity retention rate of 1.0C / 0.1C. Then replace 1.0C with 2.0C and 3.0C to obtain the capacity retention rates of 2.0C / 0.1C and 3.0C / 0.1C, respectively.
[0171] Table 1 Performance test results of Examples 1 to 8 and Comparative Examples 1 to 2
[0172]
[0173]
[0174] Continued from the table above
[0175]
[0176] From the results in Table 1, it can be seen that the A and B values in Examples 1 to 8 are relatively high, satisfying the condition of 1.2≤4×A+B<4.0, indicating that the contents of mosaic structures and small domain structures in the raw coke optical organizations in Examples 1 to 8 are relatively high, and the graphite formed after high-temperature heat treatment has fine crystallites, uniform grain size, uniform structure, and high isotropy. At the same time, the graphite negative electrode materials of Examples 1 to 8 satisfy AD / AG≥1.0, IQR≤0.25, and can form a uniform carbon coating layer. Therefore, the battery using the graphite negative electrode materials of Examples 1 to 8 can have better rate performance on the basis of maintaining capacity, and this result can also be shown by the data in Table 1. The higher the rate, the more obvious the difference.
[0177] In addition, from the comparison between Example 1 and Examples 4 to 5, it can be seen that the content of the small molecule nucleating agent should not be too high, otherwise there will be basically no large domain structure and fiber structure in the green coke, it will be difficult to graphitize, the degree of graphitization will be low, the layered structure will be disordered, and there will be many defect sites. The first formation process will consume more active lithium ions, resulting in a decrease in the first capacity and the first coulombic efficiency.
[0178] By comparing Example 1 and Example 8, it can be seen that the material obtained by graphitization using a step-by-step heating method has better performance, which may be related to the presence of a mosaic structure and a small domain structure in the raw coke.
[0179] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention is described in detail with reference to the preferred embodiments, it is not limited to those listed in the embodiments. Those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A graphite negative electrode material, characterized in that: The graphite negative electrode material comprises a graphite core and an amorphous carbon outer layer, wherein the graphite negative electrode material satisfies the conditions AD / AG≥1.0 and IQR≤0.25 after Raman testing, wherein AD / AG is the peak area ratio of the D peak and the G peak in the spectrum of the Raman test, IQR is the interquartile range of AD / AG, and the D peak is located at a wavelength of 1350cm -1 The defect peak of G peak is located at a wavelength of 1580cm -1 Characteristic peaks of ideal graphite crystal.
2. The graphite negative electrode material according to claim 1, characterized in that Includes at least one of the following features (i) to (iii): (i) the thickness of the amorphous carbon outer layer is 5 to 500 nm; (ii) The specific surface area of the graphite negative electrode material is 0.5 to 2.0 m 2 / g; (III) The tap density of the graphite negative electrode material is 0.9 to 1.4 g / cm 3 ; (iv) the Dv50 of the graphite negative electrode material is 3 to 30 μm; (V) The interlayer spacing d002 of the graphite negative electrode material is 0.3355 to 0.3400 nm; (vi) the graphitization degree of the graphite negative electrode material is 85-97%; (VII) The graphite negative electrode material has an initial charge capacity of ≥320 mAh / g at 0.1C; (VIII) The first coulombic efficiency of the graphite negative electrode material at 0.1C is ≥ 90%; (IX) The 1.0C / 0.1C capacity retention rate of the graphite negative electrode material is ≥ 70%; (10) The 2.0C / 0.1C capacity retention rate of the graphite negative electrode material is ≥55%; (XI) The 3.0C / 0.1C capacity retention rate of the graphite negative electrode material is ≥35%; (XII) The graphite core is artificial graphite; (XIII) The graphite core includes artificial graphite single particles and / or artificial graphite secondary particles.
3. A method for preparing a graphite negative electrode material, characterized in that: Includes steps: ① Adding a small molecule nucleating agent to a carbon source, and then subjecting the carbon source to a coking reaction to obtain raw coke, wherein the raw coke satisfies the condition 1.2≤4×A+B<4.0 after optical tissue detection, wherein A and B represent the contents of a mosaic structure and a small domain structure in the optical tissue, respectively; the mosaic structure is a structure in which the medium color area size in the polarized image of the optical tissue is less than 30 μm, and the small domain structure is a structure in which the medium color area size in the polarized image of the optical tissue is between 30 and 50 μm; ② subjecting the raw coke to a front-end processing step to obtain coke powder single particles or shaped secondary particles, wherein the front-end processing step includes at least one of a pulverizing step, a shaping step, a granulating step and a secondary shaping step; ③ The coke powder single particle or the shaped secondary particle is graphitized to obtain a graphitized product; ④ The graphitized product and the carbon coating agent are mixed and then carbonized to obtain a carbonized product, and the carbonized product satisfies the conditions AD / AG≥1.0 and IQR≤0.25 after Raman testing, wherein AD / AG is the peak area ratio of the D peak and the G peak in the spectrum of the Raman test, IQR is the interquartile range of AD / AG, and the D peak is located at a wavelength of 1350cm -1 The defect peak of G peak is located at a wavelength of 1580cm -1 Characteristic peaks of ideal graphite crystal.
4. The method for preparing a graphite negative electrode material according to claim 3, characterized in that: The invention comprises at least one of the following features (1) to (25): (1) The small molecule nucleating agent is 0.01 to 1.00% by mass of the carbon source; (2)A≥0.3; (3)B≥0.2; (4) The carbon source is coal tar or slurry oil; (5) The particle size of the small molecule nucleating agent is ≤50 μm; (6) The small molecule nucleating agent includes graphite fine powder, graphitizable coke fine powder, and transition metal fine powder; (7) The coking reaction is carried out in a coking tower, the pressure of the coking tower is 50 to 700 KPa, and the coking time is 8 to 30 hours; (8) The graphitization process includes graphitizing the coke powder single particles or the shaped secondary particles using a graphitization furnace; (9) The equipment used for the graphitization process is an Acheson graphitization furnace, a box-type graphitization furnace or a continuous graphitization furnace; (10) The temperature of the graphitization process is 2600-3200° C.; (11) The Dv50 of the graphitized product is 3 to 30 μm; (12) The specific surface area of the graphitized product is 0.7 to 3.0 m 2 / g; (13) The tap density of the graphitized product is 0.9 to 1.4 g / cm 3 ; (14) the carbon coating agent accounts for 0.5 to 5.0% of the quality of the graphitized product; (15) The mixing equipment includes a fusion machine, a liquid phase mixer, a V-type mixer or a high-speed VC machine; (16) The mixing speed is 50 to 1000 r / min; (17) The mixing time is 60 to 200 minutes; (18) The temperature of the carbonization process is 1000-1600° C.; (19) The carbonization process and heat preservation time is 2 to 10 hours; (20) The carbon coating agent includes at least one of petroleum asphalt, coal asphalt, natural asphalt, phenolic resin, epoxy resin, urea-formaldehyde resin, furfural phenol resin, furfuryl alcohol resin, polybutadiene resin, melamine formaldehyde resin, polyurethane, acrylic resin, lignin, starch, cellulose, sucrose and glucose; (21) After the carbonization process, the back-end processing is performed, and the back-end processing includes breaking up and screening.
5. The method for preparing a graphite negative electrode material according to claim 3, characterized in that: The coke powder single particles can be obtained by coarsely breaking, pulverizing and shaping the raw coke, the coke powder single particles are subjected to a granulation process to obtain secondary particles, and the secondary particles are subjected to a shaping process to obtain the shaped secondary particles.
6. The method for preparing a graphite negative electrode material according to claim 5, characterized in that: The method comprises at least one of the following features (i) to (iv): (i) the coarse crushing comprises crushing the green coke into particles with a diameter of 1 to 5 mm; (ii) the pulverizing-shaping comprises using a pulverizing-shaping device to pulverize and shape single coke powder particles having a Dv50 of 3 to 15 μm; (iii) the granulation step comprises granulating with a granulation kettle to obtain secondary particles with a Dv50 of 10 to 35 μm; (iv) the equipment in the granulation process is one of a drum furnace, a vertical granulation kettle, a horizontal granulation kettle and a continuous granulation kettle; (v) the temperature of the granulation step is 550° C. to 750° C.; (vi) The shaping process includes using a shaping device to shape the film until Dv50 is 10 to 33 μm.
7. The method for preparing a graphite negative electrode material according to claim 3, characterized in that: The carbon source and the small molecule nucleating agent are mixed and homogenized before the coking reaction is carried out.
8. The method for preparing a graphite negative electrode material according to claim 7, characterized in that: The homogenized material is pumped into a heating furnace through a centrifugal pump for heating, and then flows into a coking tower for the coking reaction.
9. The method for preparing a graphite negative electrode material according to claim 7, characterized in that: The heating time is 2 to 20 seconds, and the heating temperature is 450 to 600°C.
10. A secondary battery comprising a positive electrode material, a negative electrode material and an electrolyte, characterized in that: The negative electrode material comprises the graphite negative electrode material according to any one of claims 1 to 2, or the graphite negative electrode material prepared by the method for preparing the graphite negative electrode material according to any one of claims 3 to 9.